Miss Lily : a portrait of the artist Curzona Allport - Jameson, Marian; Allport, Curzona Frances Louise, 1860-1949; Allport Library and Museum of Fine Arts (Hobart, TAS : Fullers Publishing, 2018)
"Lily Allport, christened Curzona Frances Louise, was a strong woman who lived between two worlds - the old and the new. Born in the nineteenth century to a prominent Hobart family of lawyers, Lily refused to take the expected path of marriage and children. Described by her brother-in-law as 'impudent and headstrong', Lily was determined to become a professional artist. Her drive to follow her own path took her to London and success in the Royal Academy of Arts, and a satisfying life at the centre of the nineteenth-century artistic world. And then in the 1930s, at an age when she might be expected to ease up, she returned to Hobart and set up a printmaking studio, creating a late flowering of works in an entirely different medium."--Back cover.
"This book was published with the general support of the Allport Bequest and the Australian Decorative and Fine Arts Society Hobart."
NLA NL copy is signed by the author.
Includes bibliography (pages 259-261) and index.
Keywords: Allport, Curzona Frances Louise, -- 1860-1949.; Allport, Curzona Frances Louise, -- 1860-1949 -- Travel -- Europe; Allport family; Bolt Press (Tas.); Artists -- Tasmania -- Biography; Painters -- Tasmania -- Biography; Printmakers -- Tasmania -- Biography; Painting -- Tasmania -- 20th century; Painting -- England -- 19th century; Painting -- England -- 20th century; Painting, English -- 19th century; Watercolor painting -- England; Prints, Australian -- Tasmania; Fine arts: art forms; Biography: general; Tasmania -- Biography; Australian; Biographies